Implementasi Konsep Pendidikan Pesantren di Sekolah Islam Terpadu - Ropiki Iskandar, Aop (Ta'lim: The Islamic Religious Educational Journal, 2024)
The concept of pesantren education possesses strong historical and philosophical foundations within the Islamic scholarly tradition in Indonesia. In the modern era, Integrated Islamic Schools (Sekolah Islam Terpadu/SIT) have emerged as an alternative educational model that seeks to integrate the national curriculum with holistic Islamic values. This study aims to provide an in-depth analysis of how the pesantren educational concept is implemented within the SIT context, particularly in relation to curriculum dimensions, learning methods, character habituation, and the role of teachers as moral exemplars. This research employs a library research methodology through a systematic review of books, scholarly articles, curriculum documents, and previous studies. The findings indicate that the implementation of pesantren educational concepts in SIT is characterized by the strengthening of spirituality through habitual worship practices, time management grounded in adab and discipline, teacher–student relations based on an ustadziyyah model, and an integrated approach to general and religious sciences. Nevertheless, challenges remain, including adaptation to government regulations, teacher readiness, student heterogeneity, and the demand for consistently high academic quality. This study affirms that integrating the pesantren model into SIT makes possible the realization of comprehensive Islamic education, provided that it is carried out with systematic curriculum design and management.